2014
DOI: 10.3998/ark.5550190.p008.548
|View full text |Cite
|
Sign up to set email alerts
|

Radical chain reactions involving 9-alkyl-9-borafluorenes

Abstract: The preparation of 9-alkyl-9-borafluorenes and their use as radical precursors in chain reactions were investigated. These organoboranes were found to be excellent precursors of primary and secondary alkyl radicals. Reactions were readily initiated by traces of oxygen and efficient processes involving sulfonyl-based radical traps were discovered. Due to the very high reactivity of the intermediate 9-H and 9-alkyl-9-borafluorenes, problems of reproducibility were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…[bmim][PF 6 ] was directly used in the next cycle, maintaining an adequate level of efficiency even after being reused four times (94 %, 93 %, 93 %, and 92 % yield of compound 3 i). [34] Gorokhovik and co-workers [35] described the synthesis of 9alkyl-9-borafluorenes 10 and applied these boranes in the cyclohexene sulfurization (Scheme 5). Initially, the authors synthesized boranes 7 a by reacting 2,2'-dibromobiphenyl 6 a with n BuLi (2 equiv) in toluene, refluxed the sample for one hour for the lithium-bromine exchange to occur, and added boron trichloride.…”
Section: Conventional Heating Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[bmim][PF 6 ] was directly used in the next cycle, maintaining an adequate level of efficiency even after being reused four times (94 %, 93 %, 93 %, and 92 % yield of compound 3 i). [34] Gorokhovik and co-workers [35] described the synthesis of 9alkyl-9-borafluorenes 10 and applied these boranes in the cyclohexene sulfurization (Scheme 5). Initially, the authors synthesized boranes 7 a by reacting 2,2'-dibromobiphenyl 6 a with n BuLi (2 equiv) in toluene, refluxed the sample for one hour for the lithium-bromine exchange to occur, and added boron trichloride.…”
Section: Conventional Heating Methodsmentioning
confidence: 99%
“…The reactions to obtain the sulfides 12 c and 12 d are fully diastereoselective. [35] Kumar and co-workers [36] described the synthesis of diaryl selenides 3 using aryl boronic acids 2 and SeO 2 13 as a selenium source (Scheme 6). These selenium compounds 3 were prepared using boronic acids 2, selenium dioxide 13 (0.5 equiv), K 2 CO 3 (2.0 equiv), and polyethylene glycol-400 (PEG-400) as a green solvent at 110 °C for three hours.…”
Section: Conventional Heating Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Holthausen, Wagner, and coworkers later demonstrated that 9-H-9-borafluorene and its dimethyl sulfide adduct can act as hydroboration reagents for t -butylacetylene to produce the single and double hydroboration products 339 and 331 , depending on stoichiometry (Figure b). , The dimethyl sulfide adduct is a convenient reagent as it is not susceptible to ring opening oligomerization . Renaud and coworkers expanded upon the hydroboration reactivity of 9-H-9-borafluorene, demonstrating that the hydroboration products resulting from reactions of 9-H-9-borafluorene can be further functionalized by deborylation with radical sources . In this study, a series of 9-H-9-borafluorene/olefin hydroboration products were generated as intermediates which subsequently underwent radical sulfurization, oxidation, chlorination, or allylation, resulting in the net conversion of olefins to sulfides, alcohols, alkyl chlorides, or allyl-substituted alkanes, respectively (selected examples shown in Figure c and d).…”
Section: Reactivitymentioning
confidence: 99%